2020
DOI: 10.1002/mnfr.202000412
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Lipid Emulsion Determines Inflammation of the Gut‐Liver Axis, Incretin Profile, and Insulin Signaling in a Murine Model of Total Parenteral Nutrition

Abstract: Scope The aim of this study is to test whether the choice of the lipid emulsion in total parenteral nutrition (TPN), that is, n‐3 fatty acid‐based Omegaven versus n‐6 fatty acid‐based Intralipid, determines inflammation in the liver, the incretin profile, and insulin resistance. Methods and results Jugular vein catheters (JVC) are placed in C57BL/6 mice and used for TPN for 7 days. Mice are randomized into a saline group (saline infusion with oral chow), an Intralipid group (IL‐TPN, no chow), an Omegaven group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In particular, a chronic high-fat diet dramatically lowered the tight junction proteins occludin and claudin-1, while synergistically aggravating the impairment of the intestinal barrier and LPS accumulation. 58 Moreover, enormous studies indicated that the supplementation of nutrients protects the intestinal tight junction proteins against impairment, such as anthocyanins from the fruits of Lycium ruthenicum Murray. 59 We found that the intervention of HPC significantly decreased gut-derived endotoxin transfer and recovered the integrity of the intestinal barrier, which contributed to inhibiting the inflammatory response caused by intestinal leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a chronic high-fat diet dramatically lowered the tight junction proteins occludin and claudin-1, while synergistically aggravating the impairment of the intestinal barrier and LPS accumulation. 58 Moreover, enormous studies indicated that the supplementation of nutrients protects the intestinal tight junction proteins against impairment, such as anthocyanins from the fruits of Lycium ruthenicum Murray. 59 We found that the intervention of HPC significantly decreased gut-derived endotoxin transfer and recovered the integrity of the intestinal barrier, which contributed to inhibiting the inflammatory response caused by intestinal leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse experiments were performed as in Lou et al [21] and were approved by the University of Alberta Animal Policy and Welfare Committee (AUP00002007). Briefly, male C57BL/6mice aged 20 weeks and instrumented with a tunneled jugular vein catheter were purchased from Charles River Laboratories (Wilmington, MA, USA).…”
Section: Mouse Experimentsmentioning
confidence: 99%
“…Parenteral nutrition may cause insulin resistance and hyperglycemia, due to the intravenous administration of concentrated glucose [11,12,13]. In addition, in patients with short bowel syndrome, the production of incretins (a group of intestinal hormones that increase postprandial insulin secretion by pancreatic β cells) is reduced [8].…”
Section: Disruption Of Insulin Signalingmentioning
confidence: 99%
“…This may be due to the fact that the clearance of fish oil-based lipid emulsions is less dependent on LPL activity and shows favorable uptake by peripheral tissue. Studies show that n-3 PUFA counteract the negative effects of saturated fatty acids on insulin sensitivity, inflammation, and immunosuppression [13].…”
Section: Disruption Of Insulin Signalingmentioning
confidence: 99%